Rekonstruksi Prosedur Pengembangan Modul Ajar Qur'an Hadis Berbasis Problem Based Learning: Perspektif Studi Pustaka - Aisyah Hasanah; Azizah Fajri; Muhamad Yahya (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
This research was conducted to develop a step-by-step guide for creating Qur’an and Hadith learning modules using the Problem-Based Learning (PBL) method. The main issue encountered is that teachers at madrasahs do not yet have clear guidelines for creating PBL modules for the Qur’an and Hadith, so the implementation of this method in the classroom often does not succeed well. With this research, it is hoped that a guide of steps that has been tested and is in line with real conditions in the field can be produced. Theoretically, modules created through these six steps starting from analyzing needs, formulating real problems, adapting PBL syntax with the principles of ta'wil, creating a guide for teachers, seeking expert evaluation, and conducting pilot tests, can help address the issue of students who tend to be passive in their learning. This study employed a literature review method by analyzing the content of various scientific articles. As a result, the researcher successfully formulated six detailed procedural steps.